The Evolution of the Musculoskeletal Trauma Section of the Orthopaedic In-Training Examination. (12th April 2023) - Shaath, M. Kareem; Garrett, Christopher H.; Lin, Jianna; Avilucea, Frank R.; Munro, Mark W.; Langford, Joshua R.; Haidukewych, George J.
Abstract : Introduction: In 1963, the American Academy of Orthopaedic Surgeons administered the Orthopaedic In-Training Examination (OITE), the first and longest running yearly medical specialty examination. There have been no recent studies to evaluate the content of the musculoskeletal trauma section of the OITE. Methods: We analyzed all questions that were classified by the American Academy of Orthopaedic Surgeons as musculoskeletal trauma from 2012 to 2019. We recorded the number of musculoskeletal trauma questions in each examination, the topics and imaging modalities tested, the references cited, and the taxonomy classification of each question. We extrapolated from a similar musculoskeletal trauma study published in 2011 to create the previous examination cohort for comparison. Results: For the current cohort, the average number of musculoskeletal trauma questions was 43.5 questions per examination (18.4%). The most frequently tested topics were proximal tibia fractures, pediatric trauma, hip fractures, and diaphyseal femur fractures, respectively. In previous examinations, questions from T1 and 2 were tested significantly more frequently compared with the current examinations ( P < 0.001 and P = 0.02, respectively). In the current cohort, T3 questions were tested significantly more frequently than previous examinations ( P = 0.001). Previous examinations had significantly more questions without an image (36 questions per year versus 25 questions per year, P < 0.001). In current versions of the examination, radiographs are tested significantly more frequently than other imaging modalities ( P < 0.001). Discussion: The musculoskeletal trauma section of the OITE has evolved. To improve and focus study efforts, residents may use this study as a guide when preparing for the examination.